Potential impact of the science - technology park on the regional development - Dobrosavljević, Andrea; Živković, Živan (Serbian Journal of Management, 2018)
The impact of the Science and Technology Park (STP) on the development of one region can be considered through many reasons for establishment of STPs. STP represent useful instrument which creates conditions for promoting innovations, entrepreneurship, growth of knowledge-based companies, while the output results are reflected in economic growth of the region. Due to declining demographic trends in region of eastern Serbia, especially considering young population and phenomenon of “brain drain”, the goal of STP is to provide conditions for intellectual companionship at the highest level, to create chances to exchange knowledge and ideas, to improve potential of the community and to increase knowledge and achieve suitable bilateral cooperation with similar entities in the world. This paper provides review of possible benefits of establishing STP in city of Bor, based on scientific-research potential of Eastern Serbia region.